Relationship between Prescription Services and Patient Satisfaction Level at the Outpatient Installation of X Hospital, South Tangerang City - Suci Ahda Novitri; Alsyah Sholehah; Siti Yaenap; Rurynta Ferly Shavira (Pharmacy Department, Faculty of Health Sciences, UIN Syarif Hidayatullah Jakarta, Indonesia, 2025)
Prescription service is one of the pharmaceutical services that aims to improve patients' quality of life. Good service will increase patient satisfaction, affecting patients' quality of life. Patient satisfaction can be assessed by measuring elements of responsiveness, assurance, tangible, empathy, and reliability. This study aimed to determine the relationship between prescription services (waiting time) and the level of patient satisfaction at the outpatient installation of X Hospital, South Tangerang City. This study was an observational quantitative with a cross-sectional approach using a survey. The number of samples used was 382 respondents through the purposive sampling method. The data obtained were analyzed by univariate and bivariate analysis using SPSS version 22. The results showed that the level of patient satisfaction with the elements of responsiveness was 76.65%, assurance was 76.64%, tangibles was 75.28%, empathy was 76.60%, and reliability was 76.21%. Based on the results of the analysis using chi-square, there is a relationship between prescription services and the level of patient satisfaction at the outpatient installation of X Hospital, South Tangerang City with a p-value of 0.000 (p-value <0.05). This study can be concluded that there is a significant relationship between prescription services (waiting time) and the level of patient satisfaction in the outpatient installation of X Hospital, South Tangerang City.